2022
DOI: 10.1002/solr.202200359
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Degradation of 2D Dion−Jacobson Perovskites under Continuous Light Illumination

Abstract: In the past decade, there has been a rapid development in perovskite solar cells, and their highest device efficiency has reached 25.7%. But their poor stability is still one of the critical factors hindering commercialization. Compared with 3D‐structured perovskites, 2D perovskites have better structural stability especially 2D Dion−Jacobson (D–J) perovskites. However, their degradation mechanism under light is not clear. Herein, the changes in the absorption spectra of D–J perovskites (PDA(FA)n−1PbnI3n−1) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Adapted with permission. [ 137 ] Copyright 2018, Springer Nature. j) Directly evidence into the deep‐level trap states formed after white light soaking (red line) as compared with steady‐state thin (blue line) by NIR absorption measurement in the MAPbI 3 .…”
Section: Negative Effects Of Lsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted with permission. [ 137 ] Copyright 2018, Springer Nature. j) Directly evidence into the deep‐level trap states formed after white light soaking (red line) as compared with steady‐state thin (blue line) by NIR absorption measurement in the MAPbI 3 .…”
Section: Negative Effects Of Lsesmentioning
confidence: 99%
“…Zeng et al found DJ phase 2D perovskite [NH 3 (CH) 3 NH 3 ](FA) n −1 Pb n I 3 n +1 can transform to 3D α‐FAPbI 3 under continuous illumination. [ 137 ] In this process, the hydrogen bonds between the inorganic layer and the organic diammonium spacers are broken, which causes the dissociation of diammonium spacers. Afterward, α‐FAPbI 3 is formed by the inorganic layer directly in contact with the adjacent inorganic layer, and also further degrades into PbI 2 and δ‐FAPbI 3 .…”
Section: Negative Effects Of Lsesmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 However, ironically, photostability has become a major topic of discussion among researchers in the 2D perovskite research field, as it is a significant challenge to their application in optoelectronic devices. [28][29][30][31][32][33] For example, the daily used fluorescent lamps, which emit also high-energy photons at extremely low intensities, can rapidly degrade the surface structure of 2D RP perovskites. 29 In many reports, it has been also revealed that the high-energy light irradiation on perovskites can disrupt crystalline structures, leading to undercoordinated Pb states that impede carrier transport and cause substantial loss of photoluminescence (PL).…”
Section: Introductionmentioning
confidence: 99%